An overview of solid and liquid materials for adsorption-based atmospheric water harvesting. (March 2022) - Wasti, Tanzeela Z; Sultan, Muhammad; Aleem, Muhammad; Sajjad, Uzair; Farooq, Muhammad; Raza, Hafiz MU; Khan, Muhammad U; Noor, Shazia
Thermally driven adsorption-based atmospheric water harvesting (AWH) is becoming an emerging technology to provide potable water. In this regard, various adsorbent materials including solid (MOFs, silica-gels, and zeolites), liquid (CaCl2 and LiCl), and composite adsorbents are explored in the literature. This study reviews recent advancements in adsorbent materials based on their water production capacity at different conditions that is air temperature and relative humidity (RH). The MOF of type MIL-101(Cr) shows water production capacity of 3.10 L/m 2 /day at RH ranging from 10% to 40%. Similarly, Zr-MOF-808 possesses water production capacity of 8.60 L/m 2 /day at RH more than 50%. Among the studied silica-gels, mesoporous silica-gel shows highest water production capacity that is 1.30 L/m 2 /day at RH ranging from 10% to 40%. The zeolite yielded water production capacity of 0.94 L/m 2 /day at RH ranging from 10% to 40%. On the other hand, liquid adsorbents like CaCl2 + cloth, K-LiCl showed water production capacity of 3.02 L/m 2 /day, and 2.9 g/g/day, respectively at RH of about 70%. Composite adsorbent modified with binary salts and functionalized carbon nanotubes resulted water production capacity of 5.60 g/g at RH of about 35%. The study will be useful to identify the energy-efficient adsorbent for the development of sustainable AWH device.